Microscopic Chaos and Gaussian Diffusion Processes - CHEW, L. Y. (Institutional Knowledge at Singapore Management University, 2002)
In this paper, we construct and analyze a prototypical model of microscopic chaos. In particular, we extend the results of Beck and Shimizu to the case where the microscopic time scale r is no longer small. The upshot is that a non-Ornstein-Uhlenbeck deterministic process can generate a Gaussian diffusion process.